The Power of Discourse in Constructing Multicultural Society Harmony in Kampung Solor - Marselus Robot; Karolus Budiman Jama; Karus Maria Margareta; Andreas Ande; Santri E. P Djahimo (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to find out the discourse that produces a way of living together in the diversity of society in Kampung Solor, Kota Lama District, Kupang City, East Nusa Tenggara Province.  The research  method  used  is  qualitative.  The selection of  this  method  is  a consequence of the research data in the form of words, phrases, sentences and paragraphs obtained through in-depth interviews. Data analysis at the selected coding stage refers to systematization and structuration  activities.  In this  step,  the  selection  of  core  categories  or central phenomena that systemically connect to other categories is carried out, prioritizing the validity of these relationships and filling categories that require filtering and development. At this stage, a conditional matrix is created which refers to the possibility of adding or subtracting, and changing the statement of a fact based on the differences of context, condition, characteristic of social action, implication, and possible differences in perspective. The analytical framework refers to the Fairclough's perspective which focuses on three dimensions; they are text, discourse practice, and sociocultural practice. The text dimension (microstructural) is linguistically analyzed, by looking at vocabulary, semantics, and syntax. Discourse practice (mesostructural) is a dimension that deals with the process of text production and consumption. Sociocultural practice (macrostructural) is a dimension related to the context outside the text. The research findings show in the results of text analysis, discourse practice, sociocultural practice that the ideology of tolerance revealed in the discourse is:   (a) diversity is important and is God's creation. Humans only act as caretakers of diversity. (b) Diversity is a divine beauty. The task of human is to take care of the togetherness in order to strengthen social solidarity. (c) conflict resolution should be through deliberation by prioritizing humanistic feelings. In short, brotherhood is more important than differences.